Investigation of the relationship between interferon-gamma receptor 1-56C/T gene polymorphism and genetic susceptibility to lung sarcoidosis: A cross-sectional study - Serdar Kaymaz,; Murat Kavas,; Aydın Demiray,; Uğur Karasu,; Veli Çobankara,; Sibel Boğa, (Archives of Rheumatology, 2023)
Objectives: This study aims to investigate the relationship between the interferon-gamma receptor 1 (IFNGR1) polymorphism and susceptibility to lung sarcoidosis. Patients and methods: The study included a total of 55 patients (13 males, 42 females; mean age: 46.5±9.1 years; range, 22 to 66 years) with lung sarcoidosis and 28 healthy controls (6 males, 22 females; mean age: 43.9±5.9 years; range 22 to 60 years) selected from the Turkish population. The polymerase chain reaction was used for genotyping of participants to determine single-nucleotide polymorphisms. Hardy-Weinberg equilibrium, which is considered an important tool for detecting genotyping errors, was tested. Allele and genotype frequencies of patients and controls were compared using logistic regression analysis. Results: The analyses showed no correlation between the tested IFNGR1 single-nucleotide polymorphism (rs2234711) and lung sarcoidosis (p>0.05). The categorization analysis according to the clinical features, laboratory, and radiographic characteristics showed no correlation between the tested polymorphism of IFNGR1 (rs2234711) and these characteristics (p>0.05). Conclusion: The results of the study showed that the tested gene polymorphism (rs2234711) of IFNGR1 was not associated with lung sarcoidosis. More comprehensive studies are needed to verify our results.